휴경지 등에 청보리 재배 확대방안 모색 및 가치분석 - 신용광 (한국농촌경제연구원, 2007)
Roughage is the essential feed for ruminant animal. Ideal feeding ratio of roughage should be sixty percent of the total ration. However, forty percent of roughage had been fed for Korean dairy and beef cattle in 2006. It is important to expand the production and the utilization of roughage for enhancing the competitiveness of livestock products. In order to cope with current situation, the Korean government should establish a new roughage production plan. The objective of this study is to estimate an outlook of the roughage supply and demand and suggest the direction of policy option on improve roughage products. Also, this study look into the economic effects of expanding roughage production in farm and national level. The results are as follows. Firstly, the demand of roughage is estimate 5,790 thousand ton in 2015. It will supply domestic roughage(3,263 thousand ton) and import roughage(2,527 thousand ton). As new roughage production plan increase domestic roughage production up to 5,224 thousand ton, which is amount 90% of the demand of roughage in 2015. Secondly, as the roughage production increases up to 100 thousand ha, the amount of roughage import substitute is estimated to be 470 billion won. And the changed ratio reduces animal feed cost by 441 billion won. Finally, some policy directions to expand roughage production are suggested as follows: New variety and high quality roughage seeds should be supplied. The expanding roughage cropping should be considered. The government support and subsidy for roughage production organizations and farmers should be developed. Researcher: Yong-Kwang Shin, Sang-Hyen Chai. E-mail Address: ykshin22@krei.re.kr